Water sensitivity of fluorine-containing polyacrylate latex coatings: Effects of crosslinking and ambient drying conditions - Machotová, Jana; Černošková, Eva; Honzíček, Jan; Šňupárek, Jaromír (Elsevier Science BV, 2018)
In this study, fluorine-containing polyacrylate latexes comprising different levels of copolymerized perfluorethyl groups were prepared by the two-stage emulsion polymerization of 2,2,2-trifluoroethyl methacrylate, methyl methacrylate, butyl acrylate and methacrylic acid as main monomers, where the fluorine-containing monomer was copolymerized only into the second stage polymer. The effects of keto-hydrazide self-crosslinking and its combination with pre-coalescence and ionomeric crosslinking, respectively, on coating wettability, water absorption and water whitening were investigated. For the keto-hydrazide self-crosslinking, diacetone acrylamide was copolymerized into the second stage polymer to provide sites for the subsequent reaction with adipic acid dihydrazide. The pre-coalescence crosslinking of latex particles was introduced by copolymerizing allylmethacrylate during the synthesis and the ionomeric crosslinking was provided by the addition of a commercial zinc complexing agent. The influences of ambient conditions during the film-forming process in terms of temperature and relative humidity differences on coating wettability were evaluated. Further, changes of coating wettability as a function of water exposure duration were tested. The results showed that the highest level of hydrophobicity at the same amount of copolymerized 2,2,2-trifluoroethyl methacrylate could be achieved in the case of non-crosslinked latex films dried at elevated temperatures, whereas the highly crosslinked latexes combining precoalescence crosslinking and keto-hydrazide self-crosslinking provided the most water whitening-resistant coating films.
Citlivost vůči působení vody u fluorovaných polyakrylátových latexových nátěrů: Vliv síťování a vnějších podmínek při zasychání
Keywords: Latex; Fluoropolymer; Crosslinking; Coalescence; Water whitening; Wettability; latex; flouropolymer; síťování; koalescence; zbělení vodou; smáčivost